HILANGNYA KOMPAS KENDALI: ANALISIS SISTEMATIS HILANGNYA FUNGSI CONTROLLING DALAM MANAJEMEN PENDIDIKAN - Sihaloho, Fahmi Ashari S; Arifin, Syamsul (Program Studi Pendidikan Guru Sekolah Dasar Universitas Nahdlatul Ulama Sumatera Utara, 2025)
The controlling function is a crucial element within the management cycle (Planning, Organizing, Actuating, Controlling/POAC) to ensure educational goals are achieved effectively and efficiently. However, in the context of contemporary educational management, there are frequent indications of the weakening or loss of the controlling function across various levels of educational institutions. This research aims to systematically identify and analyze the causes, manifestations, and impacts of the loss of the controlling function in educational management. The study utilizes the Systematic Literature Review (SLR) method, focusing the review on relevant journal articles and books published within the last ten years. The findings of the review indicate that the loss of the controlling function often manifests through unclear performance standards, weak accountability systems, and minimal data-driven feedback. The main contributing factors include poorly managed decentralization, an organizational culture resistant to evaluation, and a lack of managerial competence in designing control systems. The implications of this functional loss are a decline in learning quality, budgetary inefficiency, and low strategic achievement within educational institutions. This research recommends the necessity of an adaptive, technology-based controlling framework, oriented towards enhancing human resources capacity in the areas of risk management and performance evaluation.